Krajobrazy wyżu depresyjnego - Żardecka, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Making a sharp distinction between depression as a malady and depression as an existential condition, and at the same time pointing to the blurring of differences between these and many other various depressive states, the paper meditates on depression and melancholia as a cultural phenomenon and as a meaningful signum temporis. It does so in a series of images, reviewing the history of the notion: the material, the palpable image of black bile, in antiquity, the moral and ascetic category of acedia in the Middle Ages and in the Baroque period, the drama of nostalgia in the age of Enlightenment and Romanticism, the quasi-strict notion of loss and bereavement in our contemporary culture, marked by the psychoanalytical paradigm.
Keywords: melancholia; żałoba; strata; strach; egzystencja; melancholy; fear; mourning; loss; existence